First-order Claims: Representing Blacks within Health Care Policies in Brazil. Issue 3 (3rd July 2019) - Lavalle, Adrian Gurza
ABSTRACT: One of the most influential and radical constructivist proposals within the recent turn to theories of representation is to recast representation as a claim, emphasising its dynamic, ubiquitous, performative and unstable nature. Such a depiction seems to render representation a highly contingent and evanescent phenomenon, though the desire to succeed leads claim-makers to seek credibility and remain attentive to context. The aim of this paper is twofold. First, it sheds light on cases where the constraining of 'context' is not exogenous, as both the audiences' criteria for judging claims and the discursive repertoire of social movements are constructed by and through processes of discursive negotiation. The article proposes to distinguish first-order and second-order claims to shed light on the endogenous relation between context and the credibility of claims. During long-term processes of discursive negotiation, the former succeed in defining as givens the moral and factual value of representative claims, granting credibility to the latter. Second, it shows how slow and piecemeal the construction of first-order claims is by looking at the case of the black feminist movement's representative claims and influence within healthcare policies in Brazil. Making claims for specific policies on racial grounds was an extremely difficult task for these movements, as such claims were at odds with the progressive, universalistic framework used by public health professionals. In addition, a discursive repertoire did not even exist within the black movement to make claims within the field of health. Mobilisation by black feminist women over a thirty-year period was crucial to both placing health at the centre of the black movement's agenda, and to growing recognition within Brazilian health policies of the importance of race.